Donor Ideology and Types of Foreign Aid - Viktor Brech; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2013)
We examine how donor government ideology influences the composition of foreign aid flows. We use data for 23 OECD countries over the period 1960-2009 and distinguish between multilateral and bilateral aid, grants and loans, recipient characteristics such as income and political institutions, tied and untied aid, and aid by sector. The results show that leftist governments increased the growth of bilateral grant aid, and more specifically grant aid to least developed and lower middle]income countries. Our findings confirm partisan politics hypotheses because grants are closely analogous to domestic social welfare transfer payments, and poverty and inequality are of greatest concern for less developed recipient countries.
Keywords: F35; F36; F53; F59; D72; C23; 330; foreign aid; government ideology; partisan politics; international organizations; panel data